A Thermal‐Reflow‐Based Low‐Temperature, High‐Pressure Sintering of Lyophilized Silk Fibroin for the Fast Fabrication of Biosubstrates. (9th August 2019) - Bucciarelli, Alessio; Chiera, Silvia; Quaranta, Alberto; Yadavalli, Vamsi K.; Motta, Antonella; Maniglio, Devid
Abstract: Solid fibroin is a bulk nonporous material that can be prepared with two methods: a liquid–gel–solid transition from a fibroin solution or a sintering procedure starting from silk powder. Both methods have their own disadvantages: the first requires several weeks and the process is size dependent; the second requires high temperatures. To overcome these limitations, a low‐temperature sintering procedure based on a thermal‐reflow is proposed in this work to produce in fast‐fashion monoliths of solid fibroin. Thermal‐reflow is a well‐known mechanism that takes place when the glass transition temperature of the material is lower than the temperature used to process it. Water plays an important role decreasing the glass transition temperature down to 40 °C. For the first time, a thermal reflow is conducted on lyophilized silk fibroin at 40 °C, associating to the water addition a high‐pressure compression. To optimize the process, a full factorial design of experiment is used. The material is then studied in the crucial phases by digital scanning calorimetry, Fourier‐transform infrared spectroscopy, and scanning electron microscopy. Finally, a mechanical characterization and a preliminary in vitro test are conducted. Abstract : A low‐temperature compression process is optimized through a design of experiment approach to produce a bulk solid material starting from dry silk fibroin in minutes. The thermal reflow, suggested by the decrease of T g, is confirmed by secondary electron microscope imaging. Using Fourier‐transform infrared spectroscopy, the role of the secondary structure is elucidated. In vitro cell culture shows large adhesion and optimal proliferation.